THE INFLUENCE OF SELF-EFFICACY, PROFFESIONAL ETHICS, AND INTEGRITY ON AUDITOR PERFORMANCE AT THE BPKP REPRESENTATIVE OF JAMBI PROVINCE - Nur Nursangkut (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2024)
Corruption in government that has continued to increase since the last 4 years shows the importance of improving the performance of government internal auditors, one of which is played by Badan Pengawas Keuangan dan Pembangunan (BPKP). This study aims to determine the effect of self-efficacy, professional ethics and integrity on auditor performance. The data used in this study are questionnaire results. The data analysis technique used is multiple linear regression analysis assisted by the SPSS version 23 program. The results of this study indicate that simultaneously the variables of selfefficacy, professional ethics and integrity affect auditor performance while partially, the self-efficacy variable has no effect on auditor performance while the professional ethics and integrity variables have a significant effect on auditor performance.